Examination of Race Disparities in Physical Inactivity among Adults of Similar Social Context - Wilson-Frederick, Shondelle M. (Ethn Dis, 2014)
OBJECTIVE: The objective of the study was to determine whether race disparities in physical inactivity are present among urban low-income Blacks and Whites living in similar social context. DESIGN: This analysis included Black and White respondents (≥18 years) from the Exploring Health Disparities in Integrated Communities-Southwest Baltimore (EHDIC-SWB; N=1350) Study and the National Health Interview Survey (NHIS; N=67790). Respondents who reported no levels of moderate or vigorous physical activity, during leisure time, over a usual week were considered physically inactive. RESULTS: After controlling for confounders, Blacks had higher adjusted odds of physical inactivity compared to Whites in the national sample (odds ratio [OR] =1.40; 95% confidence interval [CI] =1.30–1.51). In EHDIC-SWB, Blacks and Whites had a similar odds of physical inactivity (OR=1.09; 95% CI .86–1.40). CONCLUSION: Social context contributes to our understanding of racial disparities in physical inactivity.